Two new species of rain beetle (Coleoptera: Pleocomidae: Pleocoma Le Conte, 1856) in the Pacific Northwest of the United State of America - Marshall, Christopher J. (Zootaxa, 2018)
A newly discovered population of rain beetles from south central Washington, United States of America is described as Pleocoma laker Marshall, new species. The only other species known from Washington, P. crinita Linsley, 1938, is restricted to include only populations north of the Columbia River. Rain beetles from Oregon, previously considered as P. crinita, are recognized as a distinct species: Pleocoma callisto Marshall, new species. A key to the identification of all described rain beetles in Oregon and Washington is provided.